(untitled) (MAUSAM, 1970)
Hydrometeorological studies on Narmada and Tapti catchments (1969) revealed that when the Bay depressions reach central parts of Madhya Pradesh during the course of their westward movement, the lower reaches of these catchments and the Gujarat coast start receiving heavy rainfall, Attempts have, therefore, been made to find the critical position of the depressions farthest from Gujarat coast, when their influence in accentuating the monsoon rainfall along Gujarat coast is observed.